Study on the Preparation and Anisotropic Distribution of Mechanical Properties of Well-Aligned PMIA Nanofiber Mats Reinforced Composites - Bin He; Dongyi Tan; Tao Liu; Zexing Wang; Hengshu Zhou (Journal of Chemistry)
Well-aligned PMIA nanofiber mats were fabricated by electrospinning and then hot-pressing was used to produce PMIA nanofiber mats reinforced PLA matrix by layer-by-layer with the interlayer angles of 0, 45, and 90°. Orthogonal experimental design was employed to fix the effect of the hot-pressing parameters on the tensile strength of nanocomposites, and SEM was used to characterize the broken sections of the nanocomposites after tensile test. The optimized process parameters were achieved of pressure as 1000 Pa, temperature as 180°C, and time as 30 min. The SEM images of broken sections showed that the different laminate forms and the state of bearing load of nanofibers resulted in the different morphologies of broken sections. The break strength of PMIA/PLA nanocomposites with any of interlayer angles at different tensile testing directions was revealed as follows: axial > oblique > transverse, and the initial modulus also showed the same except the angle of 90° with the approach initial modulus at the axial and transverse directions. The maximum tensile strength and modulus of the nanocomposites were 17.12 MPa and 1642.17 MPa, respectively, of the axial tensile testing directions of the interlayer angle of 0°.